Non-Newtonian Canned Liquid Food, Unsteady Fluid Mechanics and Heat Transfer Prediction for Pasteurization and Sterilization - Guarda-Moraga, A; Galotto-Lopez, M; Torres-Mediano, A (2011)
Unsteady fluid mechanics and natural convective heat transfer during pasteurization and sterilization for aqueous (CMC solution) and fatty (soybean oil) liquid foods were numerically predicted by means of noncommercial computational program developed in this work. This software is based on the finite volume method and the food simulants are assumed to be non-Newtonian fluids with a temperature-dependent power-law viscosity model. Different cylindrical container materials were analyzed (LDPE, PA, PP, galvanized steel), with h/d equal to 0.53, 1.56 and 3.12. Results obtained show that the time required for sterilization is strongly dependent on the liquid food rheological behavior. A recirculating flow pattern was found inside the cylindrical container for the aqueous food stimulant. The Tshz variation with the dimensionless time was faster heating when the h/d decreases. The fastest heating pasteurization and sterilization processes were obtained for CMC solutions inside cylindrical packages with a pseudoplastic behavior. © 2010 Wiley Periodicals, Inc.